Pneumatic Coiling Actuator Inspired by the Awns of Erodium cicutarium - Geer, Ryan; Iannucci, Steven; Li, Suyi (Frontiers in Robotics and AI, 2020)
This study examines the coiling and uncoiling motions of a soft pneumatic actuator inspired by the awn tissue of Erodium cicutarium. These tissues have embedded cellulose fibers distributed in a tilted helical pattern, which induces hygroscopic coiling and uncoiling in response to the daily changes in ambient humidity. Such sophisticated motions can eventually “drill” the seed at the tip of awn tissue into the soil: a drill bit in the plant kingdom. Through finite element simulation and experimental testing, this study examines a soft pneumatic actuator that has a similar reinforcing fiber layout to the Erodium plant tissue. This actuator, in essence, is a thin-walled elastomeric cylinder covered by tilted helical Kevlar fibers. Upon internal pressurization, it can exhibit a coiling motion by a combination of simultaneous twisting, bending, and extension. Parametric analyses show that the coiling motion characteristics are directly related to the geometry of tilted helical fibers. Notably, a moderate tilt in the reinforcing helical fiber leads to many coils of small radius, while a significant tilt gives fewer coils of larger radius. The results of this study can offer guidelines for constructing plant-inspired robotic manipulators that can achieve complicated motions with simple designs.